2020
DOI: 10.1128/mbio.02023-20
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Host Arginine Is Essential for Leishmania Parasites’ Intracellular Development

Abstract: Arginine homeostasis in lysosomes is critical for the growth and metabolism of mammalian cells. Phagolysosomes of macrophages are the niche where the parasitic protozoan Leishmania resides and causes human leishmaniasis. During infection, parasites encounter arginine deprivation, which is monitored by a sensor on the parasite cell surface. The sensor promptly activates a mitogen-activated protein kinase 2 (MAPK2)-mediated arginine deprivation response (ADR) pathway, resulting in upregulating the abundance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…The CASTOR1/2 protein complex and solute carrier family38 member 9 (SLC38A9) (a lysosomal amino acid transporter) were identified as intracellular arginine sensors [ 14 , 18 , 27 ].Our bioinformatic analysis has shown that Leishmania has the homologs for SLC38A9 and components for the GATOR2 complex, normally downstream of CASTOR1/2 but we did not identify any proteins with significant CASTOR homology in Leishmania . It has been recently reported that in order to survive arginine deprivation in macrophages, Leishmania up regulates expression of its arginine transporter (AAP3) through a MAPK2-mediated arginine deprivation response (ADR) pathway [ 28 ]. As the identity of the arginine sensor that triggers the ADR pathway is unknown, it will be interesting to investigate whether the ADR pathway shares the same potential arginine sensors (SLC38A9 and a possibly unidentified protein upstream of GATOR2) with mTORC1 signaling pathway and whether the ADR pathway is downstream of or parallel to the mTORC1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The CASTOR1/2 protein complex and solute carrier family38 member 9 (SLC38A9) (a lysosomal amino acid transporter) were identified as intracellular arginine sensors [ 14 , 18 , 27 ].Our bioinformatic analysis has shown that Leishmania has the homologs for SLC38A9 and components for the GATOR2 complex, normally downstream of CASTOR1/2 but we did not identify any proteins with significant CASTOR homology in Leishmania . It has been recently reported that in order to survive arginine deprivation in macrophages, Leishmania up regulates expression of its arginine transporter (AAP3) through a MAPK2-mediated arginine deprivation response (ADR) pathway [ 28 ]. As the identity of the arginine sensor that triggers the ADR pathway is unknown, it will be interesting to investigate whether the ADR pathway shares the same potential arginine sensors (SLC38A9 and a possibly unidentified protein upstream of GATOR2) with mTORC1 signaling pathway and whether the ADR pathway is downstream of or parallel to the mTORC1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This profile has been also detected in L. infantum promastigotes [ 37 ], while an arginine downregulation has been associated with sensitive parasites growing under antimony pressure [ 36 ]. It has been suggested that Leishmania parasites can sense arginine availability regulating the expression of Leishmania arginine transporter (AAP3) under stress conditions [ 67 ]. Interestingly, there is evidence that the AAP3 transporter is upregulated at the mRNA level in Sb III -resistant parasites derived from clinical isolates [ 68 ], which could explain the tendency toward a higher arginine intracellular concentration in Sb III -resistant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania -adapted CRISPR/Cas9 system (24) to expedite disruption of the AAP3 genes, was used to create ADR mutants as described by Goldman-Pinkovich et al (23). These knockouts were obtained from the Prof. Zilberstein group (Technion-Israel Institute of Technology, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that the Leishmania donovani arginine sensor responds to arginine deprivation by activating a MAPK2-mediated signalling pathway, known as the arginine deprivation response (ADR), resulting in the up-regulation of expression and activity of its amino acid transporter 3 ( Ld AAP3) (21). Significantly, ADR is also activated during macrophage infection (21, 22, 23), indicating a role for intra-phagolysosomal arginine sensing in intracellular (amastigote) parasite survival and pathogenesis. In the present study, we have investigated the involvement of the host arginine sensing pathway by which L. donovani can gain access to the macrophage L-arginine pool.…”
Section: Introductionmentioning
confidence: 99%